The evolution and social impact of video game economics - Hart, Casey B. (Studies in new media., 2017)
This book examines how the video game industry's economic strategies have changed over the past decade (2006-2016) from a media effects and game design perspective. It also features discussions and analyses on the social impact of these changes and how consumers have reacted to evolving marketing and design strategies.